Cathodic stripping voltammetric detection and determination at a hanging mercury-drop electrode of dye contaminants in purified biomaterials: study of the human serum albumin and reactive dye 120 system - Guaratini, CCI; Zanoni, Maria Valnice Boldrin [UNESP]; Fogg, A. G. (Elsevier B.V., 2002)
Procion red HE-3B (RR120) is an example of dye currently used in affinity purification. A method is described for determining trace amounts of RR120 dye contaminant in human serum albumin by cathodic stripping voltammetry. The method is based on a measure of a well-defined peak at -0.58 V, obtained when samples of HSA protein (0.01-2% w/v) containing dye concentrations are submitted to a heating time of 330 min at 80degreesC in NaOH, pH 12.0 and the samples are removed to a solution containing Britton-Robinson buffer, pH 4.0. Using an optimum accumulation potential and tune of 0 V and 240 s, respectively, linear calibration curves were obtained from 1.0 X 10(-9) to 1.0 X 10(-8) mol 1(-1) for RR120 dye. Leakage/hydrolysis of reactive red 120 from an agarose support (e.g. at pH 2 or 12) can also be conveniently determined at very low levels (sub-mug ml(-1)) by means of cathodic stripping voltammetry, which involves adsorptive accumulation of the dye onto the hanging mercury-drop electrode. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: dye determination; human serum albumin; purified biomaterials